THE FATE OF JERUSALEMITES AT THE HANDS OF THE FIRST CRUSADE - Abu-Munshar, Maher Y. (Journal of Al-Tamaddun, 2018)
Up until July 1099CE, Muslims, Christians and Jews in Islamic Jerusalem (Bayt al-Maqdis) had lived side by side in peace. This atmosphere of peaceful co-existence dramatically changed when the army of the first Crusade arrived in the region under the pretext of liberating Jerusalem, the Christian holy places, and the tomb of Jesus from the hands of the Muslims. They were able to storm the walled city of Jerusalem and within a week, slaughter most of the Jerusalemites. This opened a new phase in the history of Islamic Jerusalem and Jerusalemites. This paper presents a critical analytical study of Muslim and Non-Muslims historical narratives dealing with the arrival of the Crusaders and the resulting fate of the Jerusalemites.